2016
DOI: 10.18632/oncotarget.12313
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections between apoptotic and autophagic pathways during thiopurine-induced toxicity in cancer cells: the role of reactive oxygen species

Abstract: Thiopurines (azathioprine, 6-mercaptopurine and 6-thioguanine) are a class of genotoxic drugs extensively used in the treatment of various illnesses including leukemia. Their underlying molecular mechanism of action involves the activation of apoptosis and autophagy but remains widely unclear. Here we present evidence that autophagy induction by thiopurines is a survival mechanism that antagonizes apoptosis and is involved in degrading damaged mitochondria through mitophagy. On the other hand, apoptosis is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(45 reference statements)
1
15
0
Order By: Relevance
“…In our study, mesalamine exerts its protective effects only during injury and not during the recovery period following DSS removal. In contrast, 6-mercaptopurine enhances autophagy solely after DSS removal, consistent with prior literature of direct effects of thiopurines in enhancing autophagy (Chaabane and Appell, 2016). While blockade of pro-inflammatory cytokines such as anti-TNF or anti-IL12/23 (Sandborn et al, 2012) represents major mechanisms for treating moderate to severe CD, it is still an open question as to whether management combining pro-inflammatory cytokine blockade (Abraham et al, 2017) with 6-mercaptopurine provides additional benefit (Colombel et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, mesalamine exerts its protective effects only during injury and not during the recovery period following DSS removal. In contrast, 6-mercaptopurine enhances autophagy solely after DSS removal, consistent with prior literature of direct effects of thiopurines in enhancing autophagy (Chaabane and Appell, 2016). While blockade of pro-inflammatory cytokines such as anti-TNF or anti-IL12/23 (Sandborn et al, 2012) represents major mechanisms for treating moderate to severe CD, it is still an open question as to whether management combining pro-inflammatory cytokine blockade (Abraham et al, 2017) with 6-mercaptopurine provides additional benefit (Colombel et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Studies have shown that cellular stress can cause autophagy, which can also lead to apoptosis ( 42 ). The various roles of these two mechanisms can be defined as the following: (i) autophagy can be used as a survival mechanism by limiting stress caused by environmental factors, and maintaining normal cell function to antagonize apoptosis ( 43 ); (ii) autophagy can also act as a promoter of apoptosis by maintaining ATP levels required for ATP-dependent apoptosis ( 44 ); (iii) autophagy can synergize apoptosis by entering into the apoptotic process and modulating caspase activity ( 45 47 ); and (iv) autophagy can also act as a “backup mechanism,” involved in the transport of damaged organelles, such as mitochondria (i.e., mitochondrial autophagy) ( 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the castration-resistant prostate cancer cells assayed in this study have decreased BRCA2 levels compared to the normal PNT1A cells, it is possible that reduced repair of 6-TG-induced DSBs by HR contributes to activation of apoptosis in cancer cells. In addition, 6-TG-mediated toxicity in cancer cells has been also associated with mitochondrial-dependent overproduction of ROS [39]. A previous study has shown that prostate cancer cells have higher ROS production compared with normal prostate cells through activation of the extramitochondrial source of ROS generator, NAD(P)H oxidase [40].…”
Section: Discussionmentioning
confidence: 99%